Association between geriatric nutritional risk index and thoracic aorta morphological changes in cancer adults underwent contrast computed tomography scans - Jian, Zhijie; Meng, Zixuan; Qiao, Xiangrui; Liu, Hui; Li, Bolin; Wu, Yue; Liu, Wenjun; Cheng, Lele (Frontiers in Nutrition, 2025)
BackgroundCancer survivors have a heightened risk of cardiovascular disease (CVD), partly associated with high rates of malnutrition, which is linked to poor cardiovascular outcomes. Changes in aortic morphology affect vascular hemodynamics and cardiovascular health. However, the relationship between malnutrition and aortic morphology in cancer patients remains unreported. This study aims to investigate the relationship between malnutrition and thoracic aorta morphological changes in cancer adults.MethodsWe performed a cross-sectional study of 189 adults without known cardiovascular disease who underwent computed tomography (CT) enhanced scan between 2020 and 2021. All patients were divided into three groups according to three categories of the geriatric nutritional risk index (GNRI): moderate to severe, GNRI of < 92 (n = 54); low, GNRI of 92–98 (n = 36); and absence of risk, GNRI of ≥98 (n = 99). The morphology of the aorta was measured by segmental diameters and tortuosity using CT.ResultsA total of 189 patients were included in the study. The average age in this study was 60.8 ± 16.5 years, with 115 men (60.8%). About half of the patients were at risk of malnutrition. Compared with the absent-risk group, participants with low or moderate to severe risk exhibited significantly larger diameters and more tortuosity of the ascending and arcus aorta, thoracic aorta, and descending thoracic aorta (all P < 0.05). We observed linear and negative associations of the GNRI value with the diameter in L1–L3 (r = −0.47, r = −0.48, r = −0.47, respectively; all P < 0.001) and tortuosity of the ascending and arcus aorta, thoracic aorta and descending thoracic aorta (r = −0.54, r = −0.53, r = −0.59, all P < 0.001). Besides, there were significant associations between malnourishment risk and morphological characteristics of the thoracic aorta in both the adjusted and unadjusted linear regression models, especially in older patients.ConclusionsOur findings indicate that malnutrition measured by GNRI is linked to aortic diameter and tortuosity in cancer patients, reflecting the exploratory role in identifying malnutrition as a novel risk marker in cardio-oncology. Future studies could explore whether improving GNRI through targeted nutritional support mitigates aortic remodeling.